High-dimensional atomic microscopy in surface plasmon polaritons*Project supported by CAS-TWAS Presidential fellowship and Chinese Scholarship Council (CSC) fellowship. (December 2020) - Munir, Akhtar; Wahab, Abdul; Jan, Munsif
Abstract : We develop a new scheme of two-dimensional (2D) and three-dimensional (3D) atom localization via absorption and gain spectra of surface plasmon polaritons (SPPs) in a closed loop four-level atomic system. For the atom–field interaction, we construct a spatially dependent field by superimposing two (three) standing-wave fields (SWFs) in 2D (3D) atom localization, respectively. We achieve high-precision and high spatial resolution of an atom localization by appropriately adjusting the system parameters such as probe field detuning and phase shifts of the SWFs. The absorption and gain spectra are used to attain information about the position of an atom in SPPs. Our proposed scheme opens up a fascinating way to improve the atom localization that supplies some practical applications in a high-dimensional SPPs.